Literature Review: The Use of The Four-Tier Diagnostic Test in Identifying Misconceptions in Physics Education - Vivin Eka Ariyanti; Reydeva Bilqis Kusuma; Aulia Yulianti (Indonesian Journal of Teacher Education, 2024)
Misconceptions in physics learning are persistent problems that hinder students from developing accurate scientific understanding. Effective identification of misconceptions requires diagnostic instruments with high precision. The Four-Tier Diagnostic Test (FTDT) has emerged as one of the most sophisticated diagnostic instruments, capable of simultaneously identifying student answers, reasoning, and their respective confidence levels. This systematic literature review aims to analyze the use of FTDT in identifying misconceptions in physics learning based on relevant studies published from 2010 to 2024. Data were collected from Google Scholar, ERIC, and Scopus databases using PRISMA guidelines. A total of 35 articles met the inclusion criteria. Results show that FTDT has been applied across seven major physics topics, with geometrical optics, Newton's laws, and electric circuits being the most frequently studied. FTDT demonstrates superior diagnostic accuracy compared to one-tier, two-tier, and three-tier tests because it can discriminate between students who truly understand, lack knowledge, hold misconceptions, or are simply guessing. The most prevalent misconceptions were identified in topics of geometrical optics, Newton's laws, electric circuits, and wave phenomena. The integration of FTDT into digital platforms has grown significantly post-pandemic. This review concludes that FTDT is a valid, reliable, and highly recommended instrument for physics misconception identification, with strong implications for designing targeted remedial instruction.